NOT AN ABSENT ORDER BUT "AN ORDERED ABSENCE": LIFE CYCLE POEMS IN MARGARET ATWOOD'S ECOPOETRY - Abolfotoh, Inas Samy (European Scientific Journal, ESJ, 2015)
Nature abuse is commonly ascribed to man's will to impose order on it. Humanity's anthropocentric violations of Nature, Margaret Atwood believes, stem from their sense of the lack of order in it or their inability to understand this order. So they begin imposing theirs as the poet highlights in "Progressive Insanities of a Pioneer" (The Animals in That Country 36-39, 1968). The poem depicts a European pioneer's disharmony and lack of unity with the wild lands of Canada. To appease his feelings of dislocation on this new land, he begins doing what he excels at: enforcing his order on the land to retain the feelings of security through controlling his unsystematic surroundings. "[D]isgusted" at hearing the random Natural sounds of "the swamp's clamourings and the outbursts / of rocks," he arrogantly declares: "This is not order / but the absence / of order. // He was wrong, the unanswering / forest implied." The "forest" assures that the pioneer is "wrong," and the poet playing with words affirms that: "It was / an ordered absence." The present paper highlights Atwood's presentation of this "ordered absence" which appears clearly in her life cycle poems in the light of Ecocriticism. The poems shed light on the poet's rhapsodic ecopoetry that celebrates a universal Natural discipline.